The Influence Of Environment, Capital, And Income Expectations On The Decision To Become An Entrepreneur Collecting Used Goods In Bengkulu City - Efendi, Muhammad Aldi Rizky; Susena , Karona Cahya; Yustanti, Nirta Vera (Innovative Business Management Journal, 2025)
This study highlights the importance of entrepreneurship as a solution to address unemployment, particularly in the scrap metal collection sector in Bengkulu City. Entrepreneurial decisions are influenced by three main factors: the environment, capital, and interrelated income expectations. The purpose of this study is to analyze the influence of the environment, capital, and income expectations simultaneously on the entrepreneurial decisions of scrap metal collectors in Bengkulu City.This research is quantitative. The sampling method used was saturated sampling. Data collection used a face-to-face method (questionnaire) with a sample of 30 respondents. This research is quantitative. The sampling method used was saturated sampling. Data collection used a face-to-face method (questionnaire) with a sample of 30 respondents. The results of the multiple linear regression analysis study Y = - 19.573 + 0.611X1 + 0.657X2 + 0.534X3 + 11.381. The regression results show that the environment (X1), capital (X2) and income expectations (X3) have a positive relationship in the same direction with investor interest. The results of the environmental test (X1) show a t count of 2.236 > t table 2.056. Significant 0.034 < 0.05, so the results of the hypothesis Ha are accepted and Ho are rejected. The results of the capital test (X2) show a t count of 2.961 < t table 2.056. Significant 0.006 > 0.05, so the results of the hypothesis Ha are accepted and Ho are rejected. The results of the income expectations test (X3) show a t count of 2.446 > t table 2.056. Significant 0.022 < 0.05, then the results of the hypothesis Ha are accepted and Ho is rejected. The results of the simultaneous F test based on the comparison of the calculated F value with F table show the calculated F value > F table, namely 12.984 > 2.975. Significant 0.000 < 0.05, then the results of the hypothesis Ha are accepted and Ho is rejected, which shows that environmental variables, capital and income expectations have a positive and significant effect simultaneously on the entrepreneurial decisions of used goods collectors in Bengkulu City.